2015
DOI: 10.1002/ceat.201400152
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Catalytic Activity of Mn‐doped Perovskite Oxides for Three‐Way Catalysis

Abstract: Mn-doped La 0.8 Sr 0.2 CoO 3 perovskite oxides (La 0.8 Sr 0.2 Co 1-x Mn x O 3 ; x = 0, 0.1, 0.3, 0.5) were synthesized by a modified sol-gel method. The phase-pure oxides were obtained. CoO and carbonates were formed on the surface of La 0.8 Sr 0.2 CoO 3 . With increasing doping content, these impurities were reduced while the stability of the perovskite structure was improved. The valence state of B-site ions and the amount of absorbed oxygen were influenced by Mn doping. The catalytic activity of the perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…There are numerous reports on Cu-containing catalysts for TWC reactions, some of which focus on controlling local Cu structures using composite oxides. Glisenti et al synthesized Cu-doped perovskite oxides, LaCo 1– x Cu x O 3 , to determine their catalytic activities for the stoichiometric CO–NO and TWC reactions . The activity for NO reduction under fuel-rich (O 2 deficient) TWC conditions was improved by Cu-doping into the perovskite structure but deteriorated in the presence of stoichiometric amount of O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports on Cu-containing catalysts for TWC reactions, some of which focus on controlling local Cu structures using composite oxides. Glisenti et al synthesized Cu-doped perovskite oxides, LaCo 1– x Cu x O 3 , to determine their catalytic activities for the stoichiometric CO–NO and TWC reactions . The activity for NO reduction under fuel-rich (O 2 deficient) TWC conditions was improved by Cu-doping into the perovskite structure but deteriorated in the presence of stoichiometric amount of O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The CO oxidation was evaluated on a Finesorb 3010 instrument with a xed-bed U-shaped quartz reactor with 3 mm internal diameter. 30 20 mg of Ag/carbon catalysts were used for each test, and the reaction temperature with a heating rate of 2 C min À1 was controlled by using a K-type thermocouple which directly contacted with the upper quartz wool near the Ag/carbon powder (Fig. S1 †).…”
Section: Catalytic Activity Evaluation Of the Hollow Ag/carbon Microp...mentioning
confidence: 99%
“…found that a La 0.8 Sr 0.2 Co 0.9 Mn 0.1 O 3 catalyst synthesized with a modified sol–gel method showed excellent CO removal performance. However, the conversions of C 3 H 8 and NO were both <50% at 500 °C under stoichiometric conditions . Garbujo et al .…”
Section: Introductionmentioning
confidence: 98%